Adhesives used in Malaysian wood industry / Mohd Shah Rizan Abdullah - Abdullah, Mohd Shah Rizan (2003)
Wood adhesive is one important element in wood-based processing industries. Most of wood products such particle board, glulam, plywood, boat construction, and more use good wood adhesive. The adhesive like urea-formaldhyde (UP), phenol- formaldhyde (PF), melamie-urea formaldhyde (MF), resorcinol formaldhyde (RF), elastomeric adhesive, thermoplastik adhesive, polyvinyl acetate and other. Each of adhesives could be use for certain wood based product. This is because the strength for each wood-based products are different. Also, the combination in adhesive contents are differences. Other than that, pH, presence of extractive, relative humidity, also contribute wood based.